Eficiência da nutrição fosfatada e análise da fluorescência transiente da clorofila a na produção de mudas de Canavalia rosea (Sw.) dc cultivadas em hidroponia - Jardim, Adriele dos Santos (2021)
Phosphorus is an essential nutrient for plant development, as it is involved in several metabolic processes in plants, in addition to being a component of structures. Therefore, the work was divided into two chapters. The first chapter aimed to evaluate the efficiency of phosphate nutrition in the production of C. rosea (Sw.) DC seedlings cultivated in hydroponics. The experimental design adopted was a randomized block design with four treatments, represented by phosphorus concentrations, 0.032; 0.125; 0.500 and 1,000 mmol L-1. At the end of the experiment, 40 days after sowing, the following were analyzed: number of fully expanded leaves, stem diameter, stem length, root volume, root length, shoot and root fresh matter mass, matter mass shoot and root dryness and calculated Dickson quality index, absorption efficiency, translocation efficiency and phosphorus utilization efficiency. Considering the efficiency of use, the ideal concentration of phosphorus for the production of C. rosea seedlings in a hydroponic system is 0.630 mmol L-1. This concentration allowed reaching 96.92% of the relative absorption efficiency, 89.69% of the Dickson quality index and 37.02% of P savings in the nutrient solution, showing the possibility of financial savings and less environmental damage in the production of seedlings of the species. In the second chapter, it is hypothesized that higher concentrations of phosphorus in nutrient solution can attenuate the effects of photoinhibition in Canavalia rosea (Sw.) DC cultivated in a hydroponic system through the analysis of transient fluorescence of chlorophyll a and the objective of evaluating the responses of C. rosea plants, subjected to different phosphorus concentrations in nutrient solution. The experimental design used was the split plot, with seven reading times as a plot and four phosphorus concentrations as a subplot, with 5 replications totaling 140 seedlings in the cultivation profiles. The parameters analyzed for transient chlorophyll a fluorescence were F0, Fm, VJ, VI, φP0, φE0, φD0, ABS/RC, TR0/RC, ET0/RC, DI0/RC, RC/CSm, PIABS and PITOTAL, in addition to OJIP curves. The OJIP curves showed typical polyphasic increase for all evaluation times as a function of phosphorus concentrations. The JIP parameters did not present significant interaction between the evaluated factors, except for PIABS. Improvements in photosynthetic parameters of C. rosea plants were observed in response to phosphorus concentrations in nutrient solution. The parameters linked to the good functioning of the photosynthetic apparatus of the plants suffered reductions in the hours of greater light intensity. The hypothesis that higher phosphorus concentrations in nutrient solution attenuates the effects of photoinhibition in C. rosea is rejected, due to the absence of significant interaction of the JIP test parameters.